Brain stimulation treatment for bipolar disorder. (21st December 2022) - Mutz, Julian
Abstract: Aims: Bipolar disorders are clinically complex, chronic and recurrent disorders. Few treatment options are effective across hypomanic, manic, depressive and mixed states and as continuation or maintenance treatment after initial symptom remission. The aim of this review was to provide an up‐to‐date overview of research on the efficacy, tolerability and cognitive effects of electroconvulsive therapy (ECT), transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), magnetic seizure therapy (MST), deep brain stimulation (DBS) and vagus nerve stimulation (VNS). Methods: References included in this review were identified through multiple searches of the Embase, PubMed/MEDLINE and APA PsycINFO electronic databases for articles published from inception until February 2022. Published reviews, meta‐analyses, randomised controlled trials and recent studies were prioritised to provide a comprehensive and up‐to‐date overview of research on brain stimulation in patients with bipolar disorders. Results: The evidence base for brain stimulation as an add‐on or alternative to pharmacological and psychological treatments in patients with bipolar disorders is limited but rapidly expanding. Brain stimulation treatments represent an opportunity to treat all bipolar disorder states, including cognitive dysfunction during euthymic periods. Conclusion: Whilst findings to date have been encouraging, larger randomised controlled trials with long‐term follow‐up are needed to clarify important questions regarding treatment efficacy and tolerability, the frequency of treatment‐emergent affective switches and effects on cognitive function.